Banapewa: banana peel as agriculture waste adsorbent in removing dye colour / Amalina Amirah Abu Bakar ... [et al.] - Abu Bakar, Amalina Amirah; Muhammad Ali, Khairul Ammar; Mat Daud, Nurhidayati; Wan Mazlan, Wan Nur Rashidah; Hamzah, Nurakmal; Badrealam, Sabariah (2022)
Researchers have recently started to concentrate on using waste materials to study the effectiveness of adsorbent media in dye colour treatment. If improperly disposed of, the wastewater from the batik textile industry can contaminate the water, thus endangering both human health and the environment. Banana peel, commonly known as Banapewa, was applied in this study as a waste adsorbent to minimise dye effluents. To ascertain the impact of varying contact time (0 to 180 minutes) and dosage, experiments were carried out at room temperature using batch study (0.05 to 0.4 g). A HACH DR2800 Spectrometer was used to determine the quantity of MB present in the samples. The results reveal that the percentage of methylene blue (MB) solution removal increases from 34.69% to 86.88% as the banana peel dosage is increased from 0.05 g to 0.3 g in 100 ml of MB solution. The optimum contact hour for the adsorption process was 150 minutes, in which 86.22% of the MB solution was removed. The kinetic research analysis shows that the adsorption of MB followed a pseudo-second order kinetic with an R2 of 0.9934. In addition, the equilibrium isotherm investigation revealed that the Freundlich model fits better than others, with an R2 of 0.7688. This suggests that Banapewa has the potential to reduce the dye concentration in batik textile industrial wastewater and furthermore could lead to reducing the dye concentration below non-drinking water standard while also providing a cost-effective, environmentally friendly adsorbent in the treatment of batik industrial wastewater. Banapewa is thus recommended for commercialisation as an alternative natural waste adsorbent.